Konsep Perlindungan Hukum di Indonesia Terhadap Hak Pasien di Rumah Rumah Sakit - Dwight Nusawakan (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2024)
This writing aims to provide an understanding to the public that patients as people who need health services at the Hospital need to get optimal services from all fields including the fulfillment of patient rights as recipients of hospital services. In order for health services to patients to take place properly, the fulfillment of patient rights at the Hospital must also be implemented so that there are no problems with health service actions to patients such as cases of malpractice or negligence. This writing uses a normative legal research approach method (normative legal research method). The normative legal research method is a library legal research conducted by examining library materials or secondary data.Thus, the patient's right as a recipient of medical services is to obtain information on medical services to find out the results of the examination/diagnosis that have been carried out by the medical team and has the right to know what actions the patient must receive.